‘What is the harm of the digital divide that must be the object of digital inclusion work and strategies? A systematic review’ - Cornelius Ewuoso (Cogent Social Sciences)
Background Many authors have published varying and sometimes competing accounts of the harm of the digital divide. These accounts are worth synthesizing in advance towards articulating the politics of the digital divide resistance.Methods This systematic review adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to synthesize evidence on the digital divide.Results Although the digital divide is not always a moral wrong, this review has found that the harm of the digital divide commonly entails capability deprivation. There are three orders of the digital divide, and these orders can occur at the macro, meso, and micro levels. The antithesis of the digital divide is digital inclusion. However, digital inclusion can fail to be empowering or address the divide if they do not address the factors that moderate the digital divide, account for the context where the digital inclusion work will be undertaken, or other variables that may have implications for the digital inclusion strategies that are developed.Discussion and Conclusion Many scholars increasingly recognise the importance of digital inclusion for flourishing today. However, a failure to articulate its harm or what must be targeted to bridge the gap could have devastating implications for the digital inclusion work.